Risk Factors for Snoring in Two Canadian First Nations Communities - James A. Dosman; Chandima P. Karunanayake; Kathleen McMullin; Sylvia Abonyi; Donna Rennie; Joshua Lawson; Shelley Kirychuk; Niels Koehncke; Jeremy Seeseequasis; Laurie Jimmy; Vivian R. Ramsden; Mark Fenton; et al. (Clocks & Sleep, 2019)
Snoring may be an important predictor of sleep-disordered breathing. Factors related to snoring among First Nations people are not well understood in a population with high rates of smoking and excess body weight. An interviewer-administered survey was conducted among 874 individual participants from 406 households in 2012 and 2013 in two Canadian First Nations communities. The survey collected information on demographic variables, individual and contextual determinants of respiratory health and snoring (classified as present versus absent) and self-reported height and weight. Multiple logistic regression analyses were conducted to examine relationships between snoring and potential risk factors adjusting for age and sex. Snoring was present in 46.2% men and 47.0% women. Considering body mass index, 259 people (30.3%) were overweight and 311 (36.4%) were considered obese. The combined current/former smoking rate was 90.2%. Being overweight, obesity, sinus trouble, current smoking status and former smoking were significantly associated with snoring. Exposure to home dampness and mold were suggestive of an association with snoring. To the degree that snoring may be a predictor of possible sleep-disordered breathing, these results indicate that environmental conditions such as smoking and home exposures may be important factors in the pathogenesis of these conditions.